Dietary disodium fumarate supplementation alleviates subacute ruminal acidosis (SARA)-induced liver damage by inhibiting pyroptosis via mitophagy-NLRP3 inflammasome pathway in lactating Hu sheep - Zhang, Hongzhu; Shi, Huimin; Zhou, Shendong; Wei, Guozhen; Xie, Wan; Meng, Meijuan; Chang, Guangjun; Shen, Xiangzhen (Frontiers in Immunology, 2023)
Liver damage is common in ruminants with subacute ruminal acidosis (SARA). Disodium fumarate (DF) could regulate rumen microbial community and neutralize ruminal organic acids. This study aimed to evaluate the effect of dietary DF supplementation on SARA-induced liver damage and investigate the underlying mechanism. Eighteen lactating Hu sheep equipped with rumen fistulas were randomly divided into 3 groups, fed a low-concentrate diet (LC group, n=6), a high-concentrate diet (HC group, n=6), and a high-concentrate diet with DF supplementation (HCDF group, n=6). Rumen pH value was measured every week. After a 2-wk adaptation period and an 8-wk experimental period, all sheep were slaughtered. Blood and liver tissue were collected for further analysis. The results showed that feeding a high-concentrate diet induced decreased rumen fluid pH and increased ruminal LPS. The rumen fluid pH in the HC group was less than 5.6 at 4 time points, indicating that SARA was successfully induced. In the HC group, we found hemorrhage and inflammatory cell infiltration in liver tissue. The contents of interleukin 1beta (IL-1β), interleukin 18 (IL-18), caspase-1, and the activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in hepatic vein were also elevated in the HC group. DF supplementation increased rumen fluid pH value, decreased ruminal LPS, attenuated hemorrhage and inflammatory cell infiltration in the liver tissue, and decreased contents of IL-1β, IL-18, caspase-1, AST, and ALT in the hepatic vein. SARA-induced increased expression of pyroptosis-related proteins (GSDMD-NT) was attenuated in the HCDF group. Meanwhile, SARA induced increased expression of mitophagy and inflammasome-related proteins (MAP1LC3-Ⅱ, PINK1, Parkin, cleaved-caspase-11, cleaved-caspase-1, NLRP3, and ASC), elevated hepatic reactive oxygen species (ROS) level, and inhibited expression of antioxidant-related genes, which was reversed by DF supplementation. Moreover, SARA activated toll-like receptor 4 (TLR4)-nuclear factor kappa B (NF-κB) signaling pathway and inhibited the entry of forkhead box A2 (FOXA2) into the nucleus, which was reversed by DF supplementation. Collectively, our data suggest that dietary DF supplementation inhibited hepatocyte pyroptosis by regulating the mitophagy-NLRP3 inflammasome pathway and the NF-κB signaling pathway, thus alleviating SARA-induced liver damage in Hu sheep.